The Splicing Factor SRSF1 as a Marker for Endothelial Senescence - Blanco, Francisco J.; Bernabeu, Carmelo (Frontiers in Physiology, 2012)
Aging is the major risk factor per se for the development of cardiovascular diseases. The senescence of endothelial cells, that line the lumen of blood vessels, is at the cellular basis of these age-dependent vascular pathologies, including atherosclerosis and hypertension. Along their lifespan, endothelial cells may reach the senescence stage by two different pathways, the replicative one derived from their finite number of divisions, and the one induced by stress stimuli. Also, certain physiological stimuli, such as TGF-β are able to modulate cellular senescence. Currently, the cellular aging process is being widely studied to identify novel molecular markers whose changes correlate with senescence. This review focuses on the regulation of alternative splicing mediated by the serine-arginine splicing factor 1 (SRSF1, or ASF/SF2) during endothelial senescence, a process that is associated with a differential subcellular localization of SRSF1, showing a scattered distribution throughout the cytoplasm. Based on its senescence-dependent involvement in alternative splicing, we postulate that SRSF1 is a key marker of endothelial cell senescence regulating the expression of alternative isoforms of target genes such as ENG, VEGFA, T3 or LMNA that integrate a common molecular senescence program.